Caracterização da zona de amortecimento da Floresta Nacional de Capão Bonito-SP - Diniz, Leonardo Silva (Universidade Federal de São Carlos, 2026)
Throughout history, humanity has been responsible for countless changes to the environment and for the excessive consumption of natural resources. In light of this, societies in various parts of the world have sought environmental restoration measures and conservation practices to achieve sustainable development that balances new technologies with the environment, with the creation of Protected Areas being one of the wolrd's primary conservation strategies. In Brazil, Law 9.985 of 2000 establishes different categories of Conservation Units. One of the mechanisms for protecting a Conservation Unit is the establishment of a surrounding area known as a Buffer Zone whose function is to filter and protect the interior of the unit from anthropogenic pressures. In light of this, the objective of this study is to analyze and characterize the Buffer Zone of the Capão Bonito National Forest through an analysis of land use and land cover, NDVI, and landscape metrics, in order to foster public debate on its importance. Through an analysis of land use and land cover in the Capão Bonito National Forest (FLONA), we identified a landscape dominated by soybean farming, with a heterogeneous matrix. Landscape metrics indicated fragmentation of the Buffer Zone, with fragments disconnected from one another and susceptible to edge effects. The current legislation governing the Buffer Zone and conflicting land use due to soybean production and the road near the Conservation Unit were also analyzed. Finally, this study presented alternatives to mitigate the impacts on the Buffer Zone. One proposed solution was the effective implementation of the Buffer Zone, expanding it to a 10 km radius around the protected area and adopting sustainable agricultural practices, such as the implementation of agroforestry systems.
Characterization of the Buffer Zone of the Capão Bonito National Forest – São Paulo
Keywords: Unidades de conservação; Zona de amortecimento; Uso e cobertura do solo; NDVI; Métricas de paisagem; Fragmentação; Conservation units; Buffer zone; Land use and land cover; NDVI; Landscape metrics; Fragmentation; Edge effect; CIENCIAS BIOLOGICAS; 15. Vida Terrestre